Adapting the DOTS Framework for Tuberculosis Control to the Management of Non-Communicable Diseases in Sub-Saharan Africa - Harries, Anthony D; Jahn, Andreas; Zachariah, Rony; Enarson, Donald (PLoS medicine, 2008)
Anthony Harries and colleagues discuss how the DOTS paradigm could be adapted for controlling diseases such as diabetes in resource-poor countries.